A história não contada da Declaração Universal dos Direitos Humanos: os caminhos do protagonismo latino-americano entre 1946 e 1948 - Pereira, Fernanda Linhares (2021)
This thesis analyzes the behind the scenes of the drafting of the Universal Declaration of Human Rights (UDHR), from 1946 to 1948. The objective of the research is to understand what was the role played by Latin Americans during the writing of one of the most important documents of the last century. To this end, we examine official documents from the United Nations: the minutes and records of transcripts of the meetings of the Preparatory Committee, the Writing Committee, the Human Rights Commission, the Economic and Social Council, the Third Plenary Committee of the General Assembly, or that is, we evaluate the documentation produced by all the bodies through which the draft declaration passed. In addition, we analyzed the draft human rights declarations submitted by numerous institutions and delegations; Constitutions submitted by United Nations member countries; the official reports of the Commissions; letters of recommendation and various documents produced by the Human Rights Commission. Furthermore, we chose to check private documents: the diaries, memoirs, autobiographies and biographies of the main members who made up the Committees and Commissions responsible for preparing the UDHR. We established between these two types of documentation the comparative method, and through it we managed to capture the network that intertwined the subjects, commissions and institutions involved in this writing process. From the analysis of this extensive documentation, it was possible to notice that Latin Americans stood out at different times, so we were able to tell another story about their role in the Commissions. We started to deal with the hypothesis, then confirmed by this Thesis, that, more than simple participation, such representatives were protagonists in the creation of UDHR. It also captured our attention, understanding why and how this protagonism (and its builders) was made impossible by the traditional historiography of human rights. In this sense, it was possible to conclude from this research that: Latin Americans were the group that made the most effort so that after the meeting in San Francisco a declaration of rights was created; at the Preparatory Committee meetings, those who first presented draft declarations (Cuban, Panamanian, Chilean); they were the most articulate and well-prepared group, both when they already brought a ready text to the United Nations like the Declaration of Bogotá, written in previous regional conventions, and when they agreed to vote together, since they were in the majority (20 Latin American delegates of a total of 59 members). In addition, your submissions of amendments and proposed amendments have given rise to numerous articles of the Declaration. We ended up weaving a story, hitherto concealed, about the prominent role played by this group. This was exposed from a structure organized in three chapters. In the first chapter, we focus on the main actors and institutions that contributed to the writing of the UDHR. In the second, we present how the phases for the preparation of the document were structured and organized. And in the third, we examine the writing of all his articles and demonstrate the indispensable collaboration of Latin Americans on all these occasions. All of this was done with the aim of answering our central problem: the role of Latin American countries in the writing of the universal text, not properly registered by the historiography of Human Rights.